The Affective Competence Scale of Primary School Teachers - Katache, Mokhtar Salim (El Omda in Linguistics and Discourse Analysis, 2025)
English translation: This article aims to introduce one of the highly important, if not decisive, competencies in the success of any educational process, namely teachers’ affective competence. After reviewing the theoretical literature on the subject, the decision was made to construct a measurement tool for this competence, as—according to the researcher’s knowledge—no study in Algeria, nor in the Arab and Islamic world, has adequately addressed this gap. Accordingly, a scale was developed to measure the affective competence of primary school teachers, based on the theoretical foundations of affective competence as presented in the works of John D. Mayer and Peter Salovey and Daniel Goleman, as well as the classification of basic emotions proposed by Paul Ekman. The study concluded by validating the scale after verifying its psychometric properties.